STABILIZATION OF THE ECOLOGICAL ENVIRONMENT - Umarov Javoxir Erkin o‘g‘li; Yusufov Sobirjon Baxrombek o‘g‘li; Арипов Нуритдин Юсупович; Kаримов Ташмухамед Халмухамедович (Web of Journals Publishing, 2024)
In this regard, it is necessary to transport waste by hydraulic means in order to prevent long-term accumulation of waste in temporary waste collection places. This will allow the waste to be easily transported to special recycling landfills in a timely manner, and various sanitary diseases will be prevented. The main criterion of the article is to create a moral environment in the reception of consumer waste, to separate them according to the structure of the waste, and to reduce the labor force and achieve economic efficiency by using a hydraulic unit.
Keywords: spiritual environment, cashiers, landfill, economic samaador and hydraulic road.